FTA shapes peatland conservation strategies in Peru - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
CIFOR worked and the government of Peru produce a report evaluating CO2 emissions from peatlands deforestation and degradation, used and was cited in the FREL submitted by the government to the UNFCCC.